A Phenol‐Amine Superglue Inspired by Insect Sclerotization Process. Issue 43 (25th August 2020) - Wang, Younseon; Jeon, Eun Je; Lee, Jeehee; Hwang, Honggu; Cho, Seung‐Woo; Lee, Haeshin
Abstract: Exoskeletons of insects formed by sclerotization processes exhibit superstrong properties in moduli. Here, it is demonstrated that mimicking the sclerotization process using phenol and polyamine molecules unexpectedly results in a 100% ecofriendly, biocompatible waterborne superglue. Oxygen presented in air and dissolved in water acts as an initiator producing phenolic radical/quinone for superglue curing. Despite synthesis‐free uses of water, phenol, and polyamine, its adhesion strength is comparable to commercial epoxy glue showing >6 MPa in lap shear strength. The phenol‐amine superglue bonds to various substrates including ceramics, woods, fabrics, plastics, metals, and importantly biological tissues. Due to strong adhesion, the superglue effectively seals wounds within a few seconds, and, due to its waterborne nature, no harmful respiratory effect is observed because of any release of volatile organic compounds. The easy, cost‐effective preparation of the phenol‐amine superglue can revolutionize varieties of industrial, biomedical, daily life processes. Abstract : A phenol/polyamine superglue (PPS) inspired by insect‐cuticle‐inspired chemistry is reported. PPS is 100% waterborne superglue with unprecedented strong adhesion (≈6 MPa) comparable to industrial epoxy glues. The key chemistry in PPS is silica‐agglomerate‐mediated phenolic oxidation and entanglement network formations. Besides the adhesion, PPS exhibits superior biocompatibility without emitting volatile organic compounds.